Economic feasibility analysis for an electric public transportation system: Two cases of study in medium sized cities in Mexico - Sánchez, José Tomás; del Río, Jesús Antonio; Sánchez, Aarón (PLOS ONE, 2022)
This work presents an economic analysis that illustrates the feasibility and the possible benefits related to the replacement of internal combustion vehicles (ICVs)by electric vehicles (EVs) public transportation in medium-sized cities. According to the current operating conditions, we calculate the cost of operating internal combustion vehicles and compare them with a selected EV with approximately the same passenger capacity. We calculate the CO2 emissions in both cases. Moreover, for the case of EV, we analyze two scenarios: 1) Use the grid to charge the EV and 2) a grid-connected photovoltaic system using the available land in the store terminals. The net present value (NPV) indicates the feasibility of two EV replacement scenarios: EV fleet using energy from the grid and EV fleet with a PV system energy generation interconnected to the grid. The economic analysis considers the different prices of electricity according to the existing tariff schemes in Mexico. Due to the electricity generation mix in Mexico, in the case of CO2 emissions, the reduction is not as expected in the only grid connection; but a PV system reduces more than 30% CO2. This analysis was carried out for two medium-sized cities: Morelia, Michoacán, and Cuernavaca, Morelos, both in Mexico.